Active drag reduction technique for enhancing the liquid-liquid mixing intensity in micromixers - Abdulbari, Hayder A. (2016)
The advancement of microfluidic devices in the past two decades have had a considerable impact on many academic and industrial fields like biomedical diagnostics, drug development, food and chemical industries. Most of the microfluidics devices consist of microchannels for liquids transportation and mixing, and the design of these channels highly controls the liquids interactions especially in the case of micromixers. The flow in the micromixers is always strictly laminar, and the mixing intensity will depend only on the molecular diffusion between the two phases. Such poor mixing efficiency will affect the micromixers design and size. Optimizing the micromixers size and design is directly related to the media type, micromixers shapes, and flowing conditions. Enhancing the liquids flow in micromixers using active drag reduction techniques will be implemented in the present work. In this work, the addition of soluble polymeric additives (Xanthan gum) function as a drag reducing agent (DRA) on the flow behavior in micromixers was investigated. Seven different geometries of Y-shaped micromixers were designed and fabricated using adapted soft lithography method. Eight different additive concentrations (20ppm to 500ppm) were used to investigate the concentration effect on the flow in the microscale devices. The maximum flow increment (%FI) of 34.90% was achieved by utilizing 500 ppm of Xanthan gum at the operating pressure of 100 mbar in micro-channel with width of 500 μm. The flow behavior of the drag reducing additive into the flow was also investigated using micro particle velocimetry (μ-PIV). It can be seen that active drag reduction technique can enhance the mixing efficiency and the liquids flow in micromixers, and that will contribute significantly to the micromixers size optimization. The experimental results show that, the new design can enhance the flow in the passive micromixer when introducing a single water phase by 28.73% within the 60 μm base-to-height ribleted micromixer at the operating pressure of 200 mbar. Secondary vortices were observed which would able to enhance the mixing intensity within the systems. The results of the present work can be very useful to country and society through enhancing the detection performance of biosensors and the conversion rates of bio-reactors through reducing the fabrication cost and improving the performance.